Analisis Kepuasan dan Loyalitas Nasabah Pengguna Bpd Bali Mobile Menggunakan Metode End User Computing Satisfaction pada Bank BPD Bali Cabang Pembantu Nusa Dua - Ni Ketut Sundari Utami; Ida Bagus Sanjaya; Laily Fauziah (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
The rapid growth of digital banking services has encouraged banks to continuously improve the quality of mobile banking applications to enhance customer satisfaction and foster long-term loyalty. This study aims to examine the influence of End User Computing Satisfaction (EUCS) on customer satisfaction and loyalty among users of the BPD Bali Mobile application at Bank BPD Bali Nusa Dua Sub-Branch, as well as to investigate the effect of customer satisfaction on customer loyalty. A quantitative research approach was employed using a simple random sampling technique involving 96 active BPD Bali Mobile users. Data were analyzed using path analysis, with EUCS measured through five dimensions: content, accuracy, format, ease of use, and timeliness. The findings indicate that respondents perceived EUCS (3.72), customer satisfaction (3.68), and customer loyalty (3.86) to be at a good level. Hypothesis testing revealed that EUCS has a positive and significant effect on customer satisfaction (β = 0.113; p < 0.001) and customer loyalty (β = 0.083; p < 0.001). Furthermore, customer satisfaction also exerts a positive and significant effect on customer loyalty (β = 0.190; p = 0.020). These findings suggest that improving the quality of the BPD Bali Mobile application to better meet users' needs enhances customer satisfaction, which subsequently strengthens customer loyalty. Therefore, Bank BPD Bali should continue optimizing its digital banking services, particularly in terms of system stability and ease of use, to improve user experience and sustain long-term customer loyalty.